1998
DOI: 10.1111/j.1348-0421.1998.tb02282.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Escherichia coli Cultured on RainbowTM Agar O157 with Particular Reference to Enterohaemorrhagic Escherichia coli (EHEC)

Abstract: RainbowTM Agar O157 is designed for the rapid isolation and identification of enterohaemorrhagic Escherichia coli (EHEC), particularly O157, characterised by black colonies. Five-hundred-eighty-five E. coli strains, including O157, O111 and O113 serogroups from many sources were examined on RainbowTM Agar O157. EHEC O157 could readily be isolated and recognized uniquely by typical black colonies. Some other EHEC also stand out as blue-black, whereas O113 and some other EHEC strains were mauve, red or pink and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Shortcomings of media for the selective cultivation of E. coli O157:H7 in test samples with heavy background growth such as sewage and river water have been reported by other researchers (Bettelheim, 1998). False-positive laboratory reports can result in delayed consideration of alternative diagnoses or therapeutic interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Shortcomings of media for the selective cultivation of E. coli O157:H7 in test samples with heavy background growth such as sewage and river water have been reported by other researchers (Bettelheim, 1998). False-positive laboratory reports can result in delayed consideration of alternative diagnoses or therapeutic interventions.…”
Section: Resultsmentioning
confidence: 99%
“…This was followed by a number of more specific media including the Rainbow Agar (Bettelheim 1998a), CHROMagar R (Bettelheim 1998b), and O157:H7 ID agar (O157 H7 ID-F) . When examining any of these media for the presence of O157 STEC, if other typical E. coli-like colonies are selected and subjected to further investigation, it is possible that some may well be non-O157 STEC.…”
Section: Isolation Identification and Characterization Of Non-o157 mentioning
confidence: 99%
“…Soon after the first description of the outbreaks due to the O157 STEC (Riley et al 1983), it was realized that these types were unusual in not being able to ferment the carbohydrate sorbitol and a medium, which had originally been developed to select for certain EPEC (Rappaport and Heng 68 K. A. BETTELHEIM Kudoh et al 1994 1952) was shown to be very effective in selecting O157 STEC from among the other commensal E. coli normally found on primary isolation of fecal specimens (March and Ratnam 1986). As ever-increasing numbers of cases and outbreaks due to O157 STEC were being reported in the world literature and even more effective media for their isolation were available (Bettelheim 1998a(Bettelheim , 1998b, it appeared that the O157 STEC were the only types of STEC of any significance. Although non-O157 STEC had been reported before 1982 (Konowalchuk et al 1977;Wade et al 1979;Wilson and Bettelheim 1980) and have regularly continued to be reported from human cases and outbreaks as well as from animals and environmental sources, very few laboratories look for them.…”
Section: Introductionmentioning
confidence: 99%
“…It contains chromogenic substances specific for fJgalactosidase and GUD. Strains of 0157 STEC characteristically produce charcoal grey or steel black colonies, typical non-0157 STEC strains are blue or purple, and most non-STEC E. coli are violet or red (Bettelheim 1998b). The addition of tellurite and novobiocin improves the recovery of E. coli 0157 on Rainbow" Agar 0157 (Stein and Bochner 1998).…”
Section: Enrichment Mediamentioning
confidence: 99%